Investigação de remanescentes de aglomerados abertos galácticos - Mateus de Souza Angelo (2017)
Galactic open star clusters are subject to disruption eects as they evolve, which cause gradual depletion of their stellar content. Their nal evolutionar are characterized by the presence of an open cluster remnant (OCR), barely distinguishable from eld stars. For this work, multi-object GMOS/Gemini-South spectroscopy was carried out for stars in the eld of 4 OCR candidates: NGC7193, ESO425- SC15, NGC7772 e ESO429-SC02. Another 17 objects classied as OCRs in the literature were studied via photometry and proper motions. Other 8 objects classied as dynamically evolved open clusters were also included in our sample, for comparison purposes. The determination of astrophysical parameters and color-magnitude decontamination procedure allowed us to conclude that NGC7193, NGC7772 and ESO425-SC15 are prototypes of OCRs and ESO429-SC02 is an asterism. Based on a joint analysis of our 20 OCRs and the 8 evolved open clusters, we concluded that OCRs are dynamically similar, since they present limiting radii less than 3 pc, masses between 1035M and velocity dispersions between 15 35 km/s. Their stellar densities follow the relation / R(2;80;1), dierently from the evolved open clusters, for which we obtained / R(1;70;4). In general, we also observed that our OCRs sample present depletion of low-mass stars, which is a signature of clustersin advanced dynamical evolutionary states. The results suggest that, after a long evolutionary history, which includes mass loss from stellar evolution and dynamical interactions, star clusters lose\memory" of their initial forming conditions and reach a remnant stage, in which their dynamical parameters are within reasonably restricted ranges. Although poorly populated, the OCRs keep characteristics of a coeval stellaraggregate. In this way, they are the nal residue of Galactic open star clusters evolution.